BANKRUPTCY PREDICTION USING ALTMAN Z-SCORE MODEL AND DATA ENVELOPMENT ANALYSIS MODEL: A CASE OF PUBLIC LISTED REALTY SECTOR COMPANIES IN INDIA - et al., ARPIT SIDHU (International Journal of Advanced Science and Technology, 2019)
Over the years, around the world, bankruptcy prediction models has gained the centre stage of attention to predict failure in corporate firms. Bankruptcy prediction in corporate has become a growing concern in India especially with the matter of fact that distress has ruled over almost all the sectors in the Indian economy in the last couple of years. The data of Insolvency and Bankruptcy Board of India (IBBI) shows that the companies in real estate and renting business have been affected the most. Therefore this study intends to estimate likelihood of Bankruptcy of real estate sector companies by applying accounting versions of Altman’s Z-Score Model and input oriented Data Envelopment Analysis (DEA) CRS Model. The study tested NSE listed Realty Sector companies which are constituent of the Nifty Realty index that are primarily engaged into construction of residential and commercial properties. Although the results produced by both the models employing different accounting parameters are not entirely the same. However both the models reveal that there is need of agility action in case of two financially distressed realty sector companies. The results of the study can be of great significance to all the stakeholders who are affected directly or indirectly by the financial performance of these companies.